Tempo de trabalho, tempo de estudo: experiências de jovens mulheres do coletivo Da Raiz ao Fruto - Cantalejo, Marriete de Sousa (Universidade Federal de São Carlos, 2026)
This study investigates the role of the Da Raiz ao Fruto Collective as a space of resistance and community care in the face of the neoliberal scenario of precarious work and social acceleration (Rosa, 2019). The central objective is to analyze to what extent the organization of the collective enables young mothers to resignify experiences of youth and other temporalities through community care. Grounded in the sociologies of time and gender, the thesis uses the categories of sexual division of labor (Kergoat, 2009) and supports (Martuccelli, 2007) to understand how the intersectionalities of race, class, and territory traverse the use of time. This qualitative research involved administering sociodemographic questionnaires to 16 young women, completing time-use diaries (referring to Wednesdays and Saturdays) with 13 participants, and conducting 13 semi-structured interviews between September 2023 and the first half of 2024. Active participant observation was also used between November 2022 and May 2024. The results show that young women tend to postpone motherhood and marriage as a strategy to increase the time dedicated to academic training, seeking to combine personal fulfillment with qualified entry into the job market. A generational "protection pact" was identified, in which the mothers of the participants assume reproductive work to enable their daughters' education. Although young women are reached by public education policies, a gap is noted in public policies focused on work and care for this population. It is concluded that, despite the overload and temporal desynchronization, the collective acts as an essential support and safe space, promoting leisure experiences and autonomy that allow young women to subvert the logic of immediacy and seek temporal emancipation.

Este estudio investiga el rol del Colectivo Da Raiz ao Fruto como espacio de resistencia y cuidado comunitario frente al escenario neoliberal de trabajo precario y aceleración social (Rosa, 2019). El objetivo central es analizar hasta qué punto la organización del colectivo permite a las madres jóvenes resignificar las experiencias de la juventud y otras temporalidades a través del cuidado comunitario. Fundamentada en las sociologías del tiempo y el género, la tesis utiliza las categorías de división sexual del trabajo (Kergoat, 2009) y apoyos (Martuccelli, 2007) para comprender cómo las interseccionalidades de raza, clase y territorio atraviesan el uso del tiempo. Esta investigación cualitativa consistió en la aplicación de cuestionarios sociodemográficos a 16 mujeres jóvenes, la cumplimentación de diarios de uso del tiempo (correspondientes a miércoles y sábados) con 13 participantes, y la realización de 13 entrevistas semiestructuradas entre septiembre de 2023 y el primer semestre de 2024. También se empleó la observación participante activa entre noviembre de 2022 y mayo de 2024. Los resultados muestran que las mujeres jóvenes tienden a posponer la maternidad y el matrimonio como estrategia para aumentar el tiempo dedicado a la formación académica, buscando combinar la realización personal con una inserción laboral cualificada. Se identificó un "pacto de protección" generacional, en el que las madres de las participantes asumen el trabajo reproductivo para posibilitar la educación de sus hijas. Si bien las mujeres jóvenes se benefician de las políticas de educación pública, se observa una brecha en las políticas públicas centradas en el trabajo y el cuidado de esta población. Se concluye que, a pesar de la sobrecarga y la desincronización temporal, el colectivo actúa como un apoyo esencial y un espacio seguro, promoviendo experiencias de ocio y autonomía que permiten a las mujeres jóvenes subvertir la lógica de la inmediatez y buscar la emancipación temporal.
Work time, study time: experiences of young women from the Da Raiz ao Fruto collective
Tiempo de trabajo, tiempo de estudio: experiencias de mujeres jóvenes del colectivo Da Raiz ao Fruto
Keywords: Tempo; Jovens; Coletivo; Trabalho; Cuidado Comunitário; Periferia; Time; Youth; Collective; Work; Community care; Periphery; Tiempo; Juventud; Colectivo; Trabajo; Cuidado Comunitario; Periferia; CIENCIAS HUMANAS::EDUCACAO; 5. Igualdade de Gênero; 10. Redução das Desigualdades; 4. Educação de Qualidade